Mucosal malignant melanoma – a clinical, oncological, pathological and genetic survey. Issue 6 (22nd March 2016) - Mikkelsen, Lauge H.; Larsen, Ann‐Cathrine; von Buchwald, Christian; Drzewiecki, Krzysztof T.; Prause, Jan U.; Heegaard, Steffen
Abstract : Mucosal melanomas constitute 1.3% of all melanomas and they may develop in any mucosal membrane. Conjunctival melanomas (0.5/million/year) and melanomas in the sinonasal cavity (0.5/million/year) are the most common, followed by anorectal melanomas (0.4/million/year) and melanomas in the oral cavity (0.2/million/year). Anorectal melanoma occurs slightly more often in females, whereas oral melanoma has a male predilection. Mucosal melanoma most commonly develops in a patient's sixth or seventh decade of life, and no differences between races have been found except for sinonasal melanoma and conjunctival melanoma, which are very rare in Black people. The symptoms are not tumour‐specific and are related to the organ system affected, and the disease is most often diagnosed at an advanced clinical stage. The diagnosis of a primary tumour is difficult, and metastatic cutaneous melanoma and choroidal melanoma must be excluded. Mutations in KIT are frequently found, while BRAF and NRAS mutations are rarely found – except in conjunctival melanomas that carry BRAF mutations. Mutations in the TERT promotor region are also found in mucosal melanomas. Complete surgical resection with free margins is the treatment of choice. The prognosis is poor, with the 5‐year survival rate ranging from 0% (gastric melanoma) to 80% (conjunctival melanoma).